Bust of Beethoven by Franz Klein - Unknown (photographer):::Creator::::::::::::; Klein, Franz, 1779-1840 (sculptor):::Contributor:::::::::::: (k. k. mil. geogr. Inst.; Vienna; Austria)
Photogravure of the bust of Beethoven by Franz Klein